THE INFLUENCE OF COMPENSATION ON INSURANCE AGENT TURNOVER INTENTION AT PT MNC LIFE ASSURANCE SALES OFFICE MEDAN - Erwansyah Erwansyah (Econosains Jurnal Online Ekonomi dan Pendidikan, 2018)
The purposes of this research are to find out about the influence of compensation on Insurance Agent Turnover Intention at PT MNC Life Assurance Sales Office Medan and to find out the impact of compensation on insurance Agent Turnover Intention, simultaneously as well as partially. The methods of this research are a descriptive and verificative method, thus the methodology of this research is descriptive survey method and explanatory survey method. The type of investigation in this research is causality. The unit of analysis of this research is individual, which are the entire agents of PT MNC Life Assurance Sales Office Medan in the amount of 60 people, which is analysis by the method of a census. A time horizon of this research is cross-sectional. The technique of the solution to this research is SPSS. The plan of data analysis of this research is path analysis, by the test plans of this research are correlation test and determination test. The result of this research is that compensation on Insurance Agent Turnover Intention in PT MNC Life Assurance Sales Office Medan is good; however, they still need reformation and improvement. Compensation simultaneously influenced on turnover intention. Keywords: compensation, turnover intention